Institutionell oordning: Om glappet i ”Museidebatten” - von Unge, Elin (Kulturella Perspektiv – Svensk etnologisk tidskrift, 2019)
In the fall of 2016 the word feud, that was later referred to ”as ”the museum debate”, took off in Swedish media. This public discussion was initiated by the Swedish journalist and China-expert Ola Wong. Within a short time span he published two articles, where he criticized the newly appointed manager of the National Museums of World Culture, Ann Follin. This museums association is a government agency organized directly under the Ministry of Culture. In his critique Wong suggested that Follin had been working too closely with the Minister of Culture, Alice Bah Kuhnke, thus compromising the political independence that conditions modern democratic cultural institutions. By using this debate as a case study, this article explores the analytical, as well as the methodological, outcomes of applying an institutional perspective to an empirical case. In doing so the focus of the study – i e the museum – is defined in comparison to other well-established societal institutions. Via this institutional perspective the analysis shows that a number of public actors experience contemporary museum work as out of place: that historical museum practises are being remodelled according to present theoretical perspectives. This fact revealed a gap between various ideas of the purposes of memory institutions, a gap here described as a form of ”institutional disorder”. In short, the debate is interpreted as a media-based negotiation, through which institutional work at museums can be challenged by, but also accommodated to, different needs in contemporary society.